Diagnosis and Therapy of Female Pelvic Organ Prolapse. Guideline of the DGGG, SGGG and OEGGG (S2e-Level, AWMF Registry Number 015/006, April 2016) - Baeßler, K.; Aigmüller, T.; Albrich, S.; Anthuber, C.; Finas, D.; Fink, T.; Fünfgeld, C.; Gabriel, B.; Henscher, U.; Hetzer, F. H.; Hübner, M.; Junginger, B.; Jundt, K.; Kropshofer, S.; Kuhn, A.; Logé, L.; Nauman, G.; Peschers, U.; Pfiffer, T.; Schwandner, O.; Strauss, A.; Tunn, R.; Viereck, V. (Geburtshilfe und Frauenheilkunde, 2016)
Aims: The aim was to establish an official interdisciplinary guideline, published and coordinated by the German Society of Gynecology and Obstetrics (DGGG). The guideline was developed for use in German-speaking countries. In addition to the Germany Society of Gynecology and Obstetrics, the guideline has also been approved by the Swiss Society of Gynecology and Obstetrics (SGGG) and the Austrian Society of Gynecology and Obstetrics (OEGGG). This is a guideline published and coordinated by the DGGG. The aim is to provide evidence-based recommendations obtained by evaluating the relevant literature for the diagnostic, conservative and surgical treatment of women with female pelvic organ prolapse with or without stress incontinence. Methods: We conducted a systematic review together with a synthesis of data and meta-analyses, where feasible. MEDLINE, Embase, Cinahl, Pedro and the Cochrane Register were searched for relevant articles. Reference lists were hand-searched, as were the abstracts of the Annual Meetings of the International Continence Society and the International Urogynecological Association. We included only abstracts of randomized controlled trials that were presented and discussed in podium sessions. We assessed original data on surgical procedures published since 2008 with a minimum follow-up time of at least 12 months. If the studies included descriptions of perioperative complications, this minimum follow-up period did not apply. Recommendations: The guideline encompasses recommendations for the diagnosis and treatment of female pelvic organ prolapse. Recommendations for anterior, posterior and apical pelvic organ prolapse with or without concomitant stress urinary incontinence, uterine preservation options, and the pros and cons of mesh placements during surgery for pelvic organ prolapse are presented. The recommendations are based on an extensive and systematic review and evaluation of the current literature and include the experiences and specific conditions in Germany, Austria and Switzerland.
Keywords: pelvic organ prolapse; stress urinary incontinence; pelvic floor; surgical therapy; physiotherapy; pessary treatment